Treasury Architecture as a Dialectical Construction in Ancient Greece: A Conceptual Evaluation of the Siphnian Treasury - Merve Yıldırımtürk; Rifat Eser Kortanoğlu (Anadolu Araştırmaları)
Ancient Greek cities dedicated a variety of valuable objects to the gods in sacred areas. The means for protecting these objects were provided by the thesauros [treasuries] they had built on behalf of their cities and were also a votive offering themself. While only cultic objects were place in temples, objects that had been dedicated by citizens and cities were kept in the treasuries. The now-lost offerings were housed by treasuries that are mentioned in ancient sources and had been built between the 7th-3rd centuries BC. Dedicated by the Greek city-states to the sacred sites of Delphi, Olympia, and Delos, the function of these structures was to protect valuable dedications to the gods and to politically demonstrate the connection the cities had to these sacred areas. The architectural details of these buildings reflect the elements of the city-state that dedicated it. This study explains the origin and meaning of the treasuries that were constructed in the sanctuaries,as well as their architectural form and function, and discusses the social, cultural, political, and economic contexts that existed between the cities and sanctuaries through the example of one of the most striking treasuries from the Archaic period, the Siphnian Treasury at Delphi (525 BC).